Split‐week gestational age model provides valuable information on outcomes in extremely preterm infants. (20th April 2020) - Thomas, Sumesh; van Dyk, Jessie; Zein, Hussein; Nettel Aguirre, Alberto; Hendson, Leonora; Church, Paige; Banihani, Rudaina; Asztalos, Elizabeth
Abstract: Aim: To compare composite outcomes of neonatal mortality or morbidity using a split‐week gestational age (GA) model to completed weeks GA maturity at 23‐26 weeks gestation. Methods: This was a retrospective cohort study of infants born at 23‐26 weeks GA. Outcomes using a split‐week GA model defined as early (X, 0‐3) and late (X, 4‐6) with X being 23‐26 weeks GA were compared to outcomes using completed weeks GA, with a similar comparison between the late split of the preceding week (X, 4‐6) and early split of the subsequent week (X + 1, 0‐3). Results: A total of 1345 infants were included in the study. Statistically significant differences were noted in outcomes between the early and late split of the gestational week at 24 (early vs late, 85.6% vs 73.0%), 25 (69.6% vs 56.6%) and 26 weeks (55.9% vs 37.4%), but not at 23 weeks GA (95.2% vs 94.5%). No statistically significant differences were noted between the late vs early part of the subsequent week (23, 4‐6) vs (24, 0‐3), and (24, 4‐6) vs (25, 0‐3) GA. Conclusion: Neonatal outcome estimates using a split week model differs from that based on the use of completed weeks of gestational maturity.